Peripheral blood mononuclear cells and regulatory T cells in acute viral hepatitis. Issue 7 (July 1985) - Barnaba, V; Tamburrini, E; Laghi, V; Cauda, R; Levrero, M; Ruocco, G; Ortona, L; Balsano, F
Abstract : During acute viral hepatitis, we observed a significant decrease in OKT4/OKT8 ratio with a significant increase in the OKT8 positive subset in acute type B and non-A-non-B hepatitis. This altered ratio persisted in type B for a long time until HBsAg antibody became detectable, while it soon returned to normal in type A and non-A-non-B hepatitis. In the majority of acute hepatitis the altered ratio is because of an increase and not to a decrease in the whole T cell population, as described in chronic HBV infection. The number of HNK-1 positive cells remained raised during the recovery phase of type B and non-A-non-B hepatitis, a finding consistent with the hypothesis that NK cells play a role in the host defence against B and non-A-non-B virus infections. Serum beta 2-microglobulin concentrations were increased only in acute hepatitis B and non-A-non-B where immunological mechanisms are suspected to be involved, and showed a good correlation with the population of activated OKIa positive cells.